Newborn Survival Analysis: between 2019 and 2021 in Burundi (London Journal of Medical and Health Research, 2025)
Progress towards the fourth Millennium Development Goal – to reduce child mortality under the age of 5, to which all countries are committed – has been slow in several countries in the Central African region in recent years. This study includes 2,886 observations from Burundi between 2019 and 2022. Early neonatal mortality (0 – 6 days) accounts for 50% of neonatal deaths in the country. Through survival analysis, I identified several key risk factors—Caesarean section, malaria, and fetal distress—as the primary causes of early neonatal mortality. Contrary to conventional wisdom, most of these health problems can be managed with cost-effective, evidence-based interventions that do not require sophisticated skills or technologies in countries with high infant mortality. By improving the health of the mother, through adequate nutrition during pregnancy, correct management of childbirth and appropriate care of the newborn, 32.9% of infant deaths can be avoided. These results further argue in favor of an appropriate prevention policy focused on the mother-child pair: better monitoring of pregnancies among mothers, ensuring good vaccination coverage and improving health infrastructure.
Keywords: Depression; antidepressants; pharmaceutical industry; psychiatric drug research; guillain barre syndrome; Chikungunya; Peripheral neuropathies; Arboviruses.; Tibial plateau fracture; anterior cruciate ligament injury; arthroscopic surgery; ligament reconstruction; Metabolically Healthy Obese (MHO); Metabolically Unhealthy Obese (MUO); Night Eating Syndrome; Sleep Pattern; Sugar-Sweetened Beverage.; west bengal; BMI.; Adolescent girls; ultra-processed foods; fat intake; menarche; menstrual health; Statistics; Burundi; Cox Model; Kaplan-Meier Model; Survival Analysis; Neonatal Mortality